2020
DOI: 10.1098/rsos.191139
|View full text |Cite
|
Sign up to set email alerts
|

The cell uptake properties and hyperthermia performance of Zn 0.5 Fe 2.5 O 4 /SiO 2 nanoparticles as magnetic hyperthermia agents

Abstract: Zn 0.5 Fe 2.5 O 4 nanoparticles (NPs) of 22 nm are synthesized by a one-pot approach and coated with silica for magnetic hyperthermia agents. The NPs exhibit superparamagnetic characteristics, high-specific absorption rate (SAR) (1083 wg −1 , f = 430 kHz, H = 27 kAm −1 ), large saturation magnetization ( M s =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
3
18
1
Order By: Relevance
“…Congruent with the current results, Wang et al obtained similar cytotoxicity for synthesized ZnF MNPs coated with silica and a diameter of 22 nm [33]. The authors evaluated the toxicity in two different cell types, at concentrations ranging from 50 to 1000 µg/mL (equivalent to 12.5 to 250 µg/cm 2 ), and observed a statistical decrease of viability starting from an exposure dose of 150 µg/cm 2 [33]. For uncoated spherical ZnF particles with an average size of 40 nm, a strong decrease in the cellular viability of cancerous cells was observed.…”
Section: Cytotoxicity Studiessupporting
confidence: 87%
See 4 more Smart Citations
“…Congruent with the current results, Wang et al obtained similar cytotoxicity for synthesized ZnF MNPs coated with silica and a diameter of 22 nm [33]. The authors evaluated the toxicity in two different cell types, at concentrations ranging from 50 to 1000 µg/mL (equivalent to 12.5 to 250 µg/cm 2 ), and observed a statistical decrease of viability starting from an exposure dose of 150 µg/cm 2 [33]. For uncoated spherical ZnF particles with an average size of 40 nm, a strong decrease in the cellular viability of cancerous cells was observed.…”
Section: Cytotoxicity Studiessupporting
confidence: 87%
“…Due to their higher surface and cytoplasmic volume, BJ cells internalized on average 2-2.5 times more ZnF01 and ZnF02 nanoparticles than their cancerous counterpart (Figure 9c,f). In a recent study, Wang et al evaluated the cellular uptake and hyperthermia performance of Zn-MNPs coated with silica and reported that the cellular internalization increases as the exposure duration increases [33]. After a 12 h incubation with an exposure dose of 200 µg/mL (equivalent to 50 µg/cm 2 ), osteosarcoma (MG-63) cells internalized a Fe 3+ quantity of 60 pg/cell [33].…”
Section: Evaluation Of Cellular Uptakementioning
confidence: 99%
See 3 more Smart Citations